Continuous glucose monitoring detected hypoglycaemia in the Treating to Target in Type 2 Diabetes Trial (4-T) - Levy, J; Davies, M; Holman, R (Elsevier, 2017)
Aims Hypoglycaemia is a significant risk in insulin treated type 2 diabetes and has been associated with future risk of cardiovascular events. We compared the frequency of low-glucose events using continuous glucose monitoring (CGM) with that of self-reported hypoglycemic events at the end of the first and third years of the Treating to Target in Type 2 Diabetes Trial (4-T), which compared biphasic, prandial and basal insulin regimens added to sulfonylurea and metformin. Methods CGM using a Medtronic Gold system was performed in a subgroup of 4-T participants. CGM detected low-glucose events were defined at thresholds of ≤3.0 (CGM3.0) and ≤2.2 (CGM2.2) mmol/l. Results Of the 110 participants, 106 and 70 had CGM analysable data at the end of years 1 and 3 respectively. In both years, the frequency of CGM detected low glucose events was several fold higher than that of self-reported hypoglycaemia (symptoms with blood glucose less than 3.1 mmol/l [<56 mg/dl]). At the end of the first year, CGM3.0 and CGM2.2 mean (95%CI) event frequencies, expressed at events per participant per year, were 120 (85, 155) and 41 (21, 61) compared with 17 (8, 29) self-reported events during CGM, each p=0.001. The disparity at the end of the third year was similar. Conclusions These data demonstrate the likely under-reporting of hypoglycaemia and of potential hypoglycaemia unawareness in clinical trials. The clinical implications of these findings need to be explored further.